PEMBELAJARAN KREATIF UNSUR MUSIK DASAR PADA ANAK DENGAN MEMANFAATKAN MEDIA DIGITAL ÃƒÂ¢Ã¢â€šÂ¬Ã…â€œCHROME MUSIC LABÃƒÂ¢Ã¢â€šÂ¬Ã‚Â - Victor Bintang Gemilang; Indar Sabri; Setyo Yanuartuti; Haris Supratno; Anik Juwariyah (Tarbiyatuna Kajian Pendidikan Islam, 2023)
Education is now starting to adapt technology in learning. Educators must begin to improve to develop themselves in creating meaningful and enjoyable learning. Like Mrs. Dra. Sugiati as a teacher at SDK Indriasana IV Surabaya who utilizes technology in learning by utilizing digital media Chrome Music Lab in music arts lessons especially to introduce students to basic musical elements consisting of tone, rhythm and harmony. The purpose of this research is to find out how the subjects teach music art and how it impacts students when using this media. Research methods with a qualitative approach to reveal objects naturally and deeply. The results of this study are that Chrome Music Lab's digital media has various features that students can use as fun media in getting to know musical elements, including; Shared Piano, Rhythm, and chords features. Learning is carried out through three stages, namely opening, core, and closing. At the opening, educators motivate students to enter into learning. At the core is learning with the media. At the end, reflection and singing are performed. Responses from students, they were very happy and interested in following the lesson carefully. Students can get to know the elements of music shown through their singing and clapping according to the tone and rhythm with the teacher.